Novel SRY-box transcription factor 9 variant in campomelic dysplasia and the location of missense and nonsense variants along the protein domains: A case report - Calvache, Carlos A.; Vásquez, Estefanía C.; Romero, Vanessa I.; Hosomichi, Kazuyoshi; Pozo, Juan C. (Frontiers in Pediatrics, 2022)
Background Campomelic dysplasia (CD) is a rare disorder that involves the skeletal and genital systems. This condition has been associated with a diverse set of mutations in the SRY-box transcription factor 9 (SOX9) gene. Case presentation We herein report a case involving a 4-year-old female patient with CD, female sex reversal, type 1 Arnold–Chiari malformation, and bilateral conductive hearing loss and investigate the causal mutation. Whole-exome sequencing analysis detected a novel Trp115X* variant in the SOX9 gene. We performed a literature review of the reported cases and demonstrated that the missense variants were located only in the self-dimerization domain (DIM) and high-mobility group box domains. We also reported that variants in the DIM domain do not cause sex reversal and identified that the amino acid sequences that were mutated in the patients with campomelic dysplasia are evolutionarily conserved among primates. Conclusions We suggest that missense variants cannot be located in the K2, PQA, and PQS given that these domains function critically for transcriptional activation or repression of target genes and evolve under purifying selection.